Factors That Influence on Online Purchase Decisions - Dwika Lodia Putri; Nurmansyah Nurmansyah; Aznuryandi Aznuryandi; Denok Sunarsi; Nurmin Arianto (Kontigensi : Jurnal Ilmiah Manajemen, 2022)
The purpose of this research is to find out what factors influence people's decisions to buy online. This research is focused on students of the Faculty of Economics, Lancang Kuning University who have made purchases online. The method of taking illustrations in this research is to use purposive sampling. The requirements that will be sampled in this research are those who have made online purchases. According to research, the majority of Lancang Kuning University students have made at least 96 purchases online. Multiple linear regression analysis was used to study the effect of four variables on online purchasing decisions. The study found that four factors - trust, security, service quality, and perceived risk - all impact online purchase decisions simultaneously. There is no clear relationship between trust, security, and quality of service and the decisions we make when buying products or services online. However, the perceived risk appears to have a significant positive effect on online purchasing decisions.